2020
DOI: 10.1093/hmg/ddaa240
|View full text |Cite|
|
Sign up to set email alerts
|

NCOA3identified as a new candidate to explain autosomal dominant progressive hearing loss

Abstract: Hearing loss is a frequent sensory impairment in humans and genetic factors account for an elevated fraction of the cases. We have investigated a large family of five generations, with 15 reported individuals presenting non-syndromic, sensorineural, bilateral and progressive hearing loss, segregating as an autosomal dominant condition. Linkage analysis, using SNP-array and selected microsatellites, identified a region of near 13 cM in chromosome 20 as the best candidate to harbour the causative mutation. After… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 77 publications
(43 reference statements)
0
13
0
Order By: Relevance
“…Finally, the last two variants (c.2909G>C in the NCOA3 gene and c.9722T>A in the P KHD1L1 gene) were located in genes encoding for proteins described as being involved in normal hearing function [ 7 , 12 ]. The variant located in PKHD1L1 co-segregated with HL only in half of the patients, while the one within the NCOA3 gene was in all the affected members of the family ( Figure 3 A), except for patient III:8 ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Finally, the last two variants (c.2909G>C in the NCOA3 gene and c.9722T>A in the P KHD1L1 gene) were located in genes encoding for proteins described as being involved in normal hearing function [ 7 , 12 ]. The variant located in PKHD1L1 co-segregated with HL only in half of the patients, while the one within the NCOA3 gene was in all the affected members of the family ( Figure 3 A), except for patient III:8 ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The Nuclear Receptor Coactivator 3 ( NCOA3 ) gene comprises 23 exons and encodes a protein of 1420 amino acids involved in the regulation of gene transcription [ 7 ]. Previous studies suggested a link between NCOA3 variants and different pathologies, such as hypertriglyceridemia, obesity and dyslipidemia [ 18 ], or an association with the progression of post-traumatic osteoarthritis, bone mass, abnormal cartilage behavior and notch signaling pathway [ 7 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations